2022
DOI: 10.3390/ijms231810320
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting Some Properties of Poly(methacrylic acid) (Nano)Composite Hydrogels by Means of Silicon-Containing Inorganic Fillers

Abstract: The present work aims to show how the main properties of poly(methacrylic acid) (PMAA) hydrogels can be engineered by means of several silicon-based fillers (Laponite XLS/XLG, montmorillonite (Mt), pyrogenic silica (PS)) employed at 10 wt% concentration based on MAA. Various techniques (FT-IR, XRD, TGA, SEM, TEM, DLS, rheological measurements, UV-VIS) were used to comparatively study the effect of these fillers, in correlation with their characteristics, upon the structure and swelling, viscoelastic, and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…As a result, loss modulus covered a range of 10 Pa to 4000 Pa, while storage modulus varied between 2500 and 25,000 Pa. This fact indicates the crosslinked behavior of the salecan hydrogels prepared with citric acid [ 53 , 54 ]. Moreover, these results indicated that the elastic character of the synthesized hydrogels ruled over the viscous character [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, loss modulus covered a range of 10 Pa to 4000 Pa, while storage modulus varied between 2500 and 25,000 Pa. This fact indicates the crosslinked behavior of the salecan hydrogels prepared with citric acid [ 53 , 54 ]. Moreover, these results indicated that the elastic character of the synthesized hydrogels ruled over the viscous character [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the -OH band narrowed in the CPMAZnO film due to the development of intermolecular hydrogen bonding and the electrostatic attraction among the two polymer chains. Moreover, the presence of an absorption band at 619 and 1409 cm −1 indicated the successful incorporation of ZnO particles within the CPMA film [9]. The crystalline structure of CPMAZnO films was analyzed and correlated with th of chitosan, PMA, and CPMA films using the XRD technique.…”
Section: Preparation and Characterization Of Cpmazno Filmsmentioning
confidence: 99%
“…Currently, poly(methacrylic acid) (PMA) has been widely considered for biomedical applications due to its nontoxicity and biocompatibility. Due to the presence of abundant carboxyl groups, PMA can be chemically modified or conjugated with other biomaterials to extend its functionality as bioactive material [9]. The antibacterial property, which is essential for effective wound healing, can be obtained by incorporating metal oxide nanoparticles in the matrix of PECs.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Ninciuleanu et al [11], focusing on the impact of adjusting some properties of poly (methacrylic acid) (nano) composite hydrogels by means of silicon-containing inorganic fillers, was also included in this Special Issue. The effect of these fillers, in correlation with their characteristics, structure and swelling, as well as the viscoelastic and water decontamination properties of (nano)composite hydrogels, were studied comparatively [11]. The experiments demonstrated that the nanocomposite hydrogel morphology was determined by the way the filler particles were dispersed in water [11].…”
mentioning
confidence: 99%
“…The effect of these fillers, in correlation with their characteristics, structure and swelling, as well as the viscoelastic and water decontamination properties of (nano)composite hydrogels, were studied comparatively [11]. The experiments demonstrated that the nanocomposite hydrogel morphology was determined by the way the filler particles were dispersed in water [11]. The structure of poly (methacrylic acid) hydrogels was also affected by the reinforcing agent through the pH of its aqueous dispersion [11].…”
mentioning
confidence: 99%